Hypervirulent Klebsiella pneumoniae (hvKp): Overview, Epidemiology, and Laboratory Detection - Dania Al Ismail; Edgar I. Campos-Madueno; Valentina Donà; Andrea Endimiani (Pathogens and Immunity)
Klebsiella pneumoniae (Kp) is a Gram-negative pathogen responsible for both hospital- and community-acquired infections. Kp is classified into 2 distinct pathotypes: classical K. pneumoniae (cKp) and hypervirulent K. pneumoniae (hvKp). First described in Taiwan in 1986, hvKp are highly pathogenic and characterized by unique phenotypic and genotypic traits. The hypermucoviscous (hmv) phenotype, generally marked by overproduction of the capsule, is often associated with hvKp, although recent studies show that some cKp strains may also have this characteristic. Furthermore, hvKp can cause severe community-acquired infections in healthy people and have been associated with metastatic infections such as liver abscess, meningitis, and endophthalmitis. HvKp are increasingly being reported in hospital-acquired settings, complicating treatment strategies. In particular, while hvKp have historically been antibiotic-susceptible, multidrug-resistant (MDR) strains have emerged and pose a significant public health threat. The combination of high virulence and limited antibiotic options demands further research into virulence mechanisms and rapid identification methods.